Why We Need Qualitative Research in Management Studies - Evelyn Lanka (RAC: Revista de Administração Contemporânea, 2020)
The purpose of this editorial is to outline the perspective of the special issue call for qualitative research tutorial papers in Revista de Administração Contemporânea (RAC), as well as to frame the need for qualitative research and its value in the larger management research literature. In this regard, this editorial will provide commentary on the concept of qualitative research and how this differs from quantitative research, before moving on to a brief discussion of why qualitative methods provide avenues for answering questions and producing research which quantitative methods may be unable to do alone. We also wish to frame the value of viewing qualitative methods as a complementary approach to quantitative methods, rather than taking a binary approach that privileges only one method or approach. This editorial does not wish to further the ongoing paradigm wars that seem to perpetually plague academic research. Rather, we wish to draw attention to the use value of qualitative research while also acknowledging the value that alternative paradigms bring. In doing so, we wish to acknowledge the continued privilege that quantitative research has in our field, and attempt to highlight ways in which qualitative research can, at times, prove to be a most useful approach, and why it may also be a valuable and necessary complement to quantitative methods. Hence, our call for qualitative research tutorial papers, which we hope will provide managers and researchers with appropriate new tools and guidance with which to conduct such complementary forms of research, and to enrich our knowledge and understanding of management.